Effectiveness of Aging Impact Management Program for Nurses with Phenomenological Approach - Kristina, Kristina (Journal of World Future Medicine, Health and Nursing, 2024)
The ageing process has a significant impact on the physical and mental well-being of caregivers, which may affect the quality of care they provide. A phenomenological approach offers an in-depth perspective in understanding individual experiences related to ageing and its impact on care practices. The purpose of this study is to explore the effectiveness of a program in managing the effect of ageing for nurses using a phenomenological approach to explore their experiences and analyze the impact of the program on care practices. The research method used was qualitative, with a phenomenological approach, to analyze qualitative data obtained from interviews. The results showed that managing the impact of the ageing program was effective in improving nurses' understanding of the ageing process and equipping them with strategies to manage its effects. The participants reported improvements in the quality of care they provided and a reduction in work-related stress. The conclusion of this study suggests that a phenomenological approach in an ageing impact management program can offer significant benefits to nurses in improving the quality of care they provide and reducing the negative impact of ageing on their overall well-being.